2019
DOI: 10.1111/nph.16168
|View full text |Cite
|
Sign up to set email alerts
|

Phospho‐mutant activity assays provide evidence for alternative phospho‐regulation pathways of the transcription factor FER‐LIKE IRON DEFICIENCY‐INDUCED TRANSCRIPTION FACTOR

Abstract: Summary The key basic helix–loop–helix (bHLH) transcription factor in iron (Fe) uptake, FER‐LIKE IRON DEFICIENCY‐INDUCED TRANSCRIPTION FACTOR (FIT), is controlled by multiple signaling pathways, important to adjust Fe acquisition to growth and environmental constraints. FIT protein exists in active and inactive protein pools, and phosphorylation of serine Ser272 in the C‐terminus, a regulatory domain of FIT, provides a trigger for FIT activation. Here, we use phospho‐mutant activity assays and study phospho‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 84 publications
0
27
0
Order By: Relevance
“…ubiquitin ligase recruitment and ubiquitination (Dubeaux et al 2018;Mithoe and Menke, 2018). Several kinases are involved in the phosphorylationdependent regulation of iron acquisition (Dubeaux et al 2018;Gratz et al 2020), and multiple phosphorylation residues have been identified in FREE1 by mass spectrometry (Zulawski et al 2013;Li et al 2019). It will be intriguing to dissect the potential links between the phosphorylation and ubiquitination of FREE1 in response to iron deficiency in the future.…”
Section: Discussionmentioning
confidence: 99%
“…ubiquitin ligase recruitment and ubiquitination (Dubeaux et al 2018;Mithoe and Menke, 2018). Several kinases are involved in the phosphorylationdependent regulation of iron acquisition (Dubeaux et al 2018;Gratz et al 2020), and multiple phosphorylation residues have been identified in FREE1 by mass spectrometry (Zulawski et al 2013;Li et al 2019). It will be intriguing to dissect the potential links between the phosphorylation and ubiquitination of FREE1 in response to iron deficiency in the future.…”
Section: Discussionmentioning
confidence: 99%
“…We could recently show that FIT phosphorylation by CIPK11 at Ser272 is a major FIT‐activating process, whereby both Ser272‐phosphorylated and non‐phosphorylated FIT forms can interact with bHLH039, with the non‐phosphorylated S272AA FIT form showing a weaker interaction with bHLH039 (Gratz, Manishankar, et al, ). Additionally, phosphorylation events at Ser221, Tyr238, and Tyr278 also affect FIT activity (Gratz, Brumbarova, et al, ). Therefore, it is possible that differential FIT phosphorylation may modulate FIT activity levels and, in turn, the effect of FIT on bHLH039 nuclear accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this heterodimerization capacity is affected by differential phosphorylation. Specifically, the heterodimerization is activated through Ser and deactivated through Tyr site phosphorylation (Gratz et al, 2020). Another Arabidopsis bHLH transcription factor, SPEECHLESS (SPCH), initiates the stomatal lineage (Simmons and Bergmann, 2016).…”
Section: Regulatory Mechanism Of Bhlhs Involved In Transcriptional Activationmentioning
confidence: 99%
“…The key bHLH transcription factor in iron (Fe) uptake, FER-LIKE IRON DEFICIENCY-INDUCED TRANSCRIPTION FACTOR (FIT), is critical for adjusting Fe acquisition to plant growth and environmental constraints (Gratz et al, 2020). Kool et al (1994) found that the bHLH133 transcription factor in rice can regulate the transport of Fe from roots to young leaves, revealing the important role of bHLH proteins in maintaining iron homeostasis in plant cells.…”
Section: Bhlhs Help Withstand Plant Iron and Copper Homeostasismentioning
confidence: 99%